Effect of graphene nanoplatelets on structural, morphological, thermal, and electrical properties of recycled polypropylene/polyaniline nanocomposites - Pang, A. L. (Springer, 2021)
Recycled polypropylene/polyaniline/graphene nanoplatelets (rPP/PANI/GNPs) nanocomposites were fabricated via ultrasonic-assisted single-screw extruder at 150–170 °C with a rotating screw speed of 50 rpm. The ultrasonic wave frequency and power supply were kept constant at a frequency of 20 kHz and 6 kW, respectively. The composition of the polymer nanocomposites used in this study was 92 wt.% rPP and 8 wt.% PANI, denoted as rPP/PANI. The effects of GNPs loadings (0.5, 1.5, and 3.0 parts per hundred resin (phr)) on the structural, morphological, thermal, and electrical properties on the nanocomposites were systematically evaluated. The X-ray diffraction (XRD) and fourier transform infrared spectroscopy (FTIR) showed the presence of GNPs characteristics at 26.5°, 42.40°, 54.51°, and interactions between GNPs and rPP/PANI nanocomposites at different GNPs loadings. The compatibility of GNPs in rPP/PANI nanocomposites was confirmed by the morphological study, which showed to an enhancement in the electrical properties of the nanocomposites. The results also showed that the incorporation of 3 phr GNPs into rPP/PANI nanocomposites resulted in a lower degree of crystallinity of about 20.8% and a higher electrical conductivity of about 4.1 × 10–1 S cm−1. The current work paves a way towards understanding how to effectively enhance the electrical conductivity of rPP/PANI nanocomposites using GNPs, leading to potential use in electronic applications.